2009
DOI: 10.1002/adma.200803683
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stress Transfer Within Double‐Walled Carbon Nanotubes Upon Their Ability to Reinforce Composites

Abstract: Stress transfer within double‐walled nanotubes (DWNTs) in a composite is followed from stress‐induced Raman band shifts. It is shown that the Raman G′ band is split into two components, one from each wall. It is found that only the G′ component from the outer wall shifts with stress, and that this will limit the ability of multiwalled nanotubes to reinforce composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 25 publications
1
69
1
Order By: Relevance
“…Huang et al [68] reported enhanced ductile behaviors in DWNTs and TWNTs submitted to axial tensions at temperatures above 2000 • C. They explain the super-elongation observed in the tubular structure as being essentially related to creep deformations of the CNTs structures at high temperatures. Windle's group confirms the same mechanical shielding of the inner tubes when multi-walled structures are submitted to strain/stress [69][70][71]. Recently, Alencar et al [72] observed the same pressure screening effects for the innermost tubes in TWNT systems.…”
Section: Double-and Triple-walled Carbon Nanotubesmentioning
confidence: 81%
“…Huang et al [68] reported enhanced ductile behaviors in DWNTs and TWNTs submitted to axial tensions at temperatures above 2000 • C. They explain the super-elongation observed in the tubular structure as being essentially related to creep deformations of the CNTs structures at high temperatures. Windle's group confirms the same mechanical shielding of the inner tubes when multi-walled structures are submitted to strain/stress [69][70][71]. Recently, Alencar et al [72] observed the same pressure screening effects for the innermost tubes in TWNT systems.…”
Section: Double-and Triple-walled Carbon Nanotubesmentioning
confidence: 81%
“…The value of  interwall was stated in earlier reports of the literature [40][41][42]. Finally,  interface is assumed to 20 MPa, as described previously [39].…”
Section: Estimation Of Multiple Fracture Of Cnt Under Tensile Loadingmentioning
confidence: 99%
“…As a result, the potential of SWCNT for use in hierarchical composites is largely unknown. Some studies, however, have shown that SWCNT offer superior performance due to their smaller diameter (or higher surface areas), higher aspect ratios, more efficient load transfer and better mechanical properties due to higher crystallinity [11,12]. On the other hand, SWCNT are known to pose challenges in terms of dispersion, requiring the development of suitable functionalization techniques which address these issues while not damaging the SWNCT molecular structure.…”
Section: Introductionmentioning
confidence: 99%